A CONTRASTIVE ANALYSIS OF CONSONANT BETWEEN ENGLISH AND BATAK TOBA LANGUAGE IN CONVERSATION - Simbolon, Putri Amelia; Hutahaean, Grace Saurma; Sitanggang, Anita (Transpublika Publisher, 2022)
Language is an indispensable communication tool. Language also a means of self-expression, a means of social adaptation in certain environments and situations. Even so, the language is very indistinct, unclear and confusing. This study will compare the consonant between English and Batak Toba language in the conversation about “Education”. This research focused to compare ten consonant in English and Batak Toba Language in conversation. A descrptive qualitative research is used in this research. The technique of analyzing data is by compare ten consonants between English and Batak Toba language in conversation “Education”. The conversation consisting of ten consonants shows the differences between English and Batak Toba Language.